Implementasi Profile Matching Untuk Rekomendasi Jenjang Karir Karyawan (Studi Kasus : Pt. Fasic Indonesia) - Siti Yuliyanti; Mira Mustika Febikusuma (LPPM Sekolah Tinggi Teknologi Indonesia Tanjungpinang, 2021)
— Information technology in the world of industry and global business which has a function as Planning and Decision where information technology enters a more strategic role because of its existence as a provider of company business plans and is an additional information for company leaders who are faced with the reality of making a number of decisions urgent. Sophisticated technology without being balanced with good Human Resources will be useless. The selection of a leader or leadership from the best employee candidates is an objective reference for determining the leader who will fill a position. Recommendations from leaders or colleagues to assess employees who will become leaders are not a guarantee and are still subjective. There needs to be a change in methods and methods as an alternative to selecting leaders according to needs. In this research, the Profile Matching method is an option to provide assessment and evaluation of employee performance to be promoted to Leader. There are three aspects in conducting the assessment and evaluation, namely the Intelligence Aspect consisting of the creative level, reasoning and solutions, ideas, concentration, and anticipation. Aspects of work attitudes have elements of accuracy, responsibility, feeling control, motivation for achievement, planning, prudence. Finally, the behavioral aspects include appropriateness, seriousness, independence and dynamic.